2022
DOI: 10.1021/acsnano.2c00688
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Reinforced Artificial Enamel by Mg2+-Induced Amorphous Intergranular Phases

Abstract: Amorphous intergranular phases in mature natural tooth enamel are found to provide better adhesion and could dramatically affect their mechanical performance as a structure reinforcing phase. This study successfully synthesized an amorphous intergranular phase enhanced fluorapatite array controlled by Mg 2+ (FAP-M) at room temperature. Furthermore, atom probe tomography (APT) observation presents that Mg 2+ is enriched at grain boundaries during the assembly of enamel-like fluorapatite arrays, leading to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This composite shows a several-fold enhancement of PLA toughness as well as outstanding improvement in load-bearing capacity and viscoelastic figure of merit, which can be attributed to the amorphous phase of alumina as well as the lamellar structure . Recently, the use of amorphous TiO 2 and intergranular ACP phase for mechanical enhancement in artificial biomaterials was also demonstrated. , …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This composite shows a several-fold enhancement of PLA toughness as well as outstanding improvement in load-bearing capacity and viscoelastic figure of merit, which can be attributed to the amorphous phase of alumina as well as the lamellar structure . Recently, the use of amorphous TiO 2 and intergranular ACP phase for mechanical enhancement in artificial biomaterials was also demonstrated. , …”
Section: Discussionmentioning
confidence: 92%
“…89 Recently, the use of amorphous TiO 2 and intergranular ACP phase for mechanical enhancement in artificial biomaterials was also demonstrated. 75,90…”
Section: Discussionmentioning
confidence: 99%
“…High resolution TEM (HRTEM) images of these nanoparticles showed no lattice fringe, suggesting that they were amorphous, which could act as the precursor for subsequent attachment to FAP crystallites. 36 To characterize the grown FAP on the enameloid substrate at an early stage, a thin lamella from a sample after reaction for 12 h was prepared with FIB, milling from the surface down to the enameloid. According to the TEM image, the underlying natural enameloid crystallites below the red dotted rectangular box were homogeneous and each crystallite possessed a distinct outline, while many 5–10 nm electron-lucent nanopores appeared on the grown FAP crystallites in a vague shape, as indicated by white arrows in the upper region in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human enamel was investigated, to analyse the Mg K-edge, and was compared with Mg ACP [ 92 , 193 ], revealing similarities in the enamel structure, as well as comparisons with rodent enamel, showing the presence of Mg in the crystallite cores. These results were combined with other nanocharacterisation techniques, such as APT and TEM, to model the amelogenesis process, as well as to provide detail about residual stress in enamel crystallites from chemical gradients [ 193 , 671 ], Figure 8 i. It was suggested that residual stress leads to an increase in the solubility of crystallite cores compared to the surrounding, which was visualised as a preferential demineralisation of the crystallites.…”
Section: Synchrotron (Circular Particle Accelerator)mentioning
confidence: 99%